CLINICAL CHARACTERISTICS OF PAEDIATRIC MEASLES PATIENTS AT MOJOWARNO CHRISTIAN HOSPITAL, JOMBANG, IN 2015-2016 - Yuda Pradana (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
Background: Measles is one of the main causes of child mortality. In 2016 there were 6,890 cases of measles with 4 patients died in Indonesia. There were 122 cases in Jombang, East Java in 2009. Aim: To describe the clinical characteristics of measles in children patients at Mojowarno Christian Hospital, Jombang, East Java. Methods: A cross sectional study using secondary data from medical records at Mojowarno Christian Hospital, Jombang, East Java, in 2015-2015. Demographic and clinical characteristics were described using tables. Results: There are 22 cases of measles in children, 3 of them had not taken measles vaccination. Most cases occurred in between 0 to 5 years old (59.1%). The proportion of measles were equal between male and female. There is a higher proportion of patients with normal nutrition status (59.1%) compared to other with malnutrition (40.9%). The most common symptoms and signs are fever (95.5%), cough (23.7%), and coryza (22.3%). The leukocyte examination mostly shows normal results for leukocyte (63.6%) and lymphocyte (50%). Conclusion: Most of the cases were presented with milder symptoms, signs and laboratory examination. There is a high prevalence of undernutrition among the subjects, which need further attention from local governments. In addition, there is a concerning high proportion of vaccinated children contracting the disease.